Cultivation of safflower flower stems with seeds treated by thermotherapy: Safflower flower stems - Menegaes, Janine Farias; Nunes, Ubirajara Russi; Bellé, Rogério Antônio; Backes, Fernanda Alice Antonello Londero; Paranhos, Juçara Terezinha; Lopes, Sidinei José (Comunicata Scientiae, 2020)
The floral stems of safflower (Carthamus tinctorius L.) present an ornamental character due to their rusticity and versatility of use. The propagation via seeds shows high incidence of pathogens, negatively affecting the establishment of plants in the field, requiring treatments. Thus, the objective of this study was to evaluate the cultivation of safflower flower stems from seeds treated by thermotherapy and sown at different seasons in the year. The experiment was carried out in a completely randomized, 4 x 3 factorial design (sowing dates and thermotherapy treatments), with four replications. Sowings took place in the first seasonal fortnights (spring and summer of 2016, and autumn and winter of 2017), after undergoing thermotherapy treatment or not: control (without treatment), moist heat thermotherapy (45º C 15 min-1) and heat dry thermotherapy (45º C 24 h-1). It was evaluated the emergence of seedlings for plant stand formation, the phenological stages until flowering, the duration of the cultivation cycle, phyllochron, anthochron, the biometry of flower stems and inflorescences. It was observed that the seed treatments via thermotherapy were beneficial for the initial establishment of seedlings in the field. The development and duration of the cultivation cycle of the flower stems were different for all sowing dates, with the maintenance of the ornamental characteristics and the quality of the flower stems.